Surface Functionalization of Nanostructured Porous Silicon by APTS: Toward the Fabrication of Electrical Biosensors of Bacterium Escherichia coli - Recio-Sanchez, G.; Dominguez-Canizares, G.; Manso, M.; Preda, I.; Torres-Costa, V.; Gutierrez, A.; Soriano, L.; J. Martin-Palma, R. (Current Nanoscience, 2011)
Nanostructured porous silicon (nanoPS) basically consists in a network of silicon nanocrystals with high specific surface. Its intrinsic high surface reactivity makes nanoPS a very suitable material for the development of biosensors. In this work, the surface of nanoPS was functionalized by the use of (3-aminopropyl)triethoxysilane solutions in toluene. Escherichia coli (E. coli) antibodies were subsequently immobilized on the functionalized surfaces. Finally, fragments of this bacterium, which are specifically recognized by the antibodies, were immobilized. Moreover, devices with a metal/nanoPS/semiconductor/metal structure were fabricated aiming at the electrical biosensing of E. Coli bacterium. The experimental results showed a strong variation of the current as a function of the presence/ absence of bacterium E. Coli and surface concentration.
Keywords: Electrical Biosensors